PENILAIAN KINERJA JARINGAN PIPA DISTRIBUSI AIR MINUM DESA KAJARHARJO KECAMATAN KALIBARU (STUDI KASUS-JARINGAN PIPA AIR BERSIH HIPPAM KAJARHARJO) - Dimas Aji Purnomo (Nusantara Hasana Journal, 2023)
Banyuwangi Regency is one of the regions at the eastern tip of the island of Java, which is located at the eastern tip of East Java Province, which has 24 subdistricts and 2,775 villages. One of them is Kalibaru District which is experiencing an increase in the need for clean water, especially in Kajarharjo Village. With this research, it is hoped that it can provide alternative solutions to clean water problems for the Kajarharjo Village area, Kalibaru District. The aim of this study is to determine the magnitude of the need for clean water in Kajarharjo Village until 2025. This research uses primary data and secondary data by projecting the population of Kajarharjo Village until 2025. The results of this analysis are the projected number of people from the calculation results in 2025 numbering 13971 people with a water demand figure of 3.75 ltr with a pipe network with a main distribution pipe cross-section of Ø 5 inches and a secondary distribution pipe cross-section of Ø 4 inches. From the results of the analysis carried out using the EPANET 2.0 program, there is a fairly significant comparison of the water weight points at each pipe connection, this proves that the topographic situation in the service area is a hilly area.